Characteristics and testing of two‐component grout in tunnelling applications. Issue 1 (17th February 2022) - Todaro, Carmine; Martinelli, Daniele; Boscaro, Alessandro; Carigi, Andrea; Saltarin, Simone; Peila, Daniele
Abstract: Two‐component grout is nowadays the most popular backfilling technique, used widely in rock or soil thanks to its versatility and the undoubted advantages for operatives compared to other backfilling technologies. Despite its intensive adoption in shielded tunnelling projects, very poor and often fragmented information is available, especially on the engineering properties used for the mix design calibration (design phase) and secondly on construction sites as the acceptance protocol (operative phase). In this work, starting from real construction sites data, an analysis has been performed in order to determine the intrinsic characteristics of the two‐component grout technology. Moreover, the most frequently used engineering parameters have been identified to characterise both component A and the hardened grout, correlated with their usage frequency. The outcomes illustrate that although at the current time different choices are made at different construction sites, a pattern of tests has been recognised, that can be considered as a significant cornerstone for the characterisation of two‐component grout.